Should I stay or should I go?: the rhetoric of "scorned political wives" - Reeder, Mal, author; Burgchardt, Carl R., advisor; Carcasson, Martin, 1972-, committee member; Sloane, Sarah, committee member (Colorado State University. Libraries, 2010)
This thesis examines the rhetoric of Elizabeth Edwards and Jenny Sanford, two "scorned political wives." In the wake of their husbands' extramarital affairs, Edwards and Sanford needed to respond to embarrassing and identity-challenging rhetorical situations. Forced to defend their choices as wives and mothers, Edwards and Sanford answered the question, "Should I stay or should I go?" Although their persuasive purposes were quite different, Edwards and Sanford each employed effective rhetoric to heighten their credibility and restore their place in society. Elizabeth Edwards chose to preserve her marriage, while Jenny Sanford decided to sever her marital bonds. By examining the themes and persuasive strategies each woman used to meet her overall goals, this thesis uncovers lines of argument, or topoi, that may be characteristic of an emerging genre of "scorned political wives."
Keywords: Edwards, Elizabeth, 1949-2010; Sanford, Jenny, 1962-; women; wives; Sanford; rhetoric; politics; Edwards; Politicians' spouses -- United States; Adultery -- United States